2007
DOI: 10.1073/pnas.0611141104
|View full text |Cite
|
Sign up to set email alerts
|

Modulating seed β-ketoacyl-acyl carrier protein synthase II level converts the composition of a temperate seed oil to that of a palm-like tropical oil

Abstract: ␤-Ketoacyl-acyl carrier protein (ACP) synthase II (KASII) elongates 16:0-ACP to 18:0-ACP in the plastid, where it competes with three other enzymes at the first major branch point in fatty acid biosynthesis. Despite its key metabolic location, the influence of KASII in determining seed oil composition remains unclear, in part because the biochemical consequences of the fab1-1 mutation were unresolved. Thus, fab1-1, and a newly identified knockout allele, fab1-2, were analyzed in the context of the hypothesis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 28 publications
4
115
0
4
Order By: Relevance
“…Our alignment and phylogenetic analyses showed that the AtKAS2 (At1g74960) gene encodes a functional protein having KAS II activity, being consistent with the complementation experiment of leaky fab1-1 mutant (Carlsson et al, 2002) and with the recently reported fatty-acid composition of knockout fab1-2 mutant (Pidkowich et al, 2007). Thus, AtKAS2 catalyzes the elongation of 16:0-ACP to 18:0-ACP in plastids, and may have many important biological functions in various tissues in various developmental stages.…”
Section: Enzymatic Function and Localization Of Atkas2supporting
confidence: 51%
“…Our alignment and phylogenetic analyses showed that the AtKAS2 (At1g74960) gene encodes a functional protein having KAS II activity, being consistent with the complementation experiment of leaky fab1-1 mutant (Carlsson et al, 2002) and with the recently reported fatty-acid composition of knockout fab1-2 mutant (Pidkowich et al, 2007). Thus, AtKAS2 catalyzes the elongation of 16:0-ACP to 18:0-ACP in plastids, and may have many important biological functions in various tissues in various developmental stages.…”
Section: Enzymatic Function and Localization Of Atkas2supporting
confidence: 51%
“…The plants were transformed according to Clough and Bent's method (Clough and Bent, 1998) using Agrobacterium tumefaciens strain GV3101. We identified individual T1 seeds carrying the transgenes by the fluorescence emitted (Stuitje et al, 2003) upon illumination with green light from an X5 LED flashlight (Inova) in conjunction with a 25A red camera filter (Pidkowich et al, 2007). A WILD M3Z dissection microscope equipped with an Olympus U-LH100HG illumination system was used to discriminate between seeds carrying Zs-Green and Ds-Red markers with the use of filters fluorescein isothiocyanate 535 and fluorescein isothiocyanate 515, respectively.…”
Section: Arabidopsis Growth and Transformationmentioning
confidence: 99%
“…Two such lines were recently reported in which fab1 was suppressed, one by hairpin RNA interference (RNAi; Pidkowich et al, 2007) and the other by a novel method of suppression termed hairpin-antisense (HPAS) RNAi (Nguyen and Shanklin, 2009). These lines contain strongly elevated seed 16:0 accumulation levels at 42% and 46%, respectively (Fig.…”
mentioning
confidence: 99%
“…Hasil studi pada tanaman model A. thaliana menunjukkan bahwa penurunan tingkat aktivitas enzim KASII sudah mencukupi untuk mengkonversi minyak pada biji Arabidopsis menyerupai karakteristik minyak kelapa sawit (Pidkowich et al, 2007). Penggunaan promoter yang diekspresikan spesifik pada mesocarp kelapa sawit (mesocarp-specific promoter) dan aplikasi metode antisense RNA dari gen KASII dan gen palmitoyl-ACP thio esterase diharapkan menghasilkan tanaman transgenik dengan komposisi minyak yang kaya akan asam lemak tak jenuh seperti asam oleat.…”
Section: Kemajuan Dan Potensi Aplikasiunclassified